Murder, Inc. : the CIA under John F. Kennedy - Johnston, James H., 1944- (Potomac Books, an imprint of the University of Nebraska Press, 2019)
"A chronological narrative of the CIA's assassination operations during the Kennedy Administration"-- Provided by publisher
Keywords: United States. -- Central Intelligence Agency -- History -- 20th century.; United States. -- Central Intelligence Agency -- Corrupt practices.; Kennedy, John F. -- (John Fitzgerald), -- 1917-1963.; Kennedy, John F. -- (John Fitzgerald), -- 1917-1963; United States. -- Central Intelligence Agency; Intelligence service -- United States -- History -- 20th century.; Assassination -- United States -- History.; United States -- Foreign relations -- 1961-1963.; Assassinat -- États-Unis -- Histoire.; États-Unis -- Relations extérieures -- 1961-1963.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; HISTORY -- United States -- 20th Century.; Assassination; Corruption; Diplomatic relations; Intelligence service; United States; 1900-1999; History